The Role of Price Perception in Interest in Buying Smartphones Through Optimization of Product Quality and Brand Image - Feliks Anggia Binsar Kristian Panjaitan; Juharsah; Amirul Afif Muhamat; Unika Oktaviani Damau; Hotman Panjaitan (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Business actors must be free to determine product prices, which of course must be proportional to the quality of the products offered, this is important because businesses often ignore product quality when emphasizing price perceptionsPurpose: The goal of this research was to assess the impact of product quality, brand image, and price perceptions on consumer purchasing interest, as well as if pricing perceptions are an effective mediator.Design/methodology/approach: Structural Equation Modeling was then used to examine the data. Findings/Result: The data indicate that product quality and price perception both positively influence purchasing intention, although price perception does not. Price perception, according to research, influences the relationship between product quality and brand image on purchase intention. Conclusion: According to this study, smartphone product quality with appealing features, durability, and cheap prices increases consumer purchasing interest.Originality/value (State of the art): Many studies have examined consumers' buying interest, but few have examined price perception as a mediating factor, particularly when it comes to buying interest. The purpose of this study was to close this gap and develop a model that included price perception as a mediating variable.